Chickpea (Cicer arietinum) oil extraction using supercritical CO2 (evaluation of the effects of temperature and pressure on yield) (Research, Society and Development, 2025)
The present research aimed to evaluate the yield of extracts of lipid content obtained from chickpeas using supercritical CO2 generating an extraction kinetic curve, to evaluate the effects of process variables (pressure and temperature), and compare with the yield of extracts using the conventional method (extraction with organic solvent). Chickpea (Cicer arietinum) is a legume rich in lipid material, being a food with an excellent nutritional rate of proteins, rich in other properties such as iron and antioxidants, widely produced in the center-west of Brazil and in other countries of the world such as India, a crop well adapted to the dry climate with low relative humidity rate in the air, very common characteristics of tropical regions, its main variety of species produced and consumed in Brazil is the Kabuli, among its main physical characteristics we have its feathery foliage with small oval leaflets, small flowers with white or purplish coloration, its plant can reach a height that varies from 30 to 60 cm, the chickpea is rich in vegetable protein, fiber and iron, it is used as a food base mainly in regions such as Asia and the Mediterranean. From this, the chickpea oil was extracted using two extraction methods, namely the conventional method, in which organic solvents are used, and the supercritical extraction method, in which supercritical fluids are used. For the conventional method, ethanol was used as the organic solvent, while for the supercritical extractionCO2was used. The results obtained show that the extraction with ethanol had a yield of approximately 6.97% of oil after a period of 8 hours. In contrast, the extraction with supercritical CO2 obtained yields of 5.57% after a time of only 80 minutes. Although the extraction with ethanol produced slightly higher yields, supercritical CO2 was more effective because the extraction process was faster. The CO2 in a supercritical state had a higher degree of efficiency because it reached its maximum yield in a significantly shorter period of time than the method using ethanol as a solvent.